Mutation of kvrA causes OmpK35/36 porin downregulation and reduced meropenem/vaborbactam susceptibility in KPC-producing Klebsiella pneumoniae - Dulyayangkul, Punyawee; Wan Ahmad Kamil, Wan Nur Ismah; Douglas, Edward J. A.; Avison, Matthew B. (American Society for Microbiology, 2020)
Meropenem-vaborbactam resistance in Klebsiella pneumoniae isolates is associated with loss-of-function mutations in the OmpK35 and OmpK36 porins. We identify two previously unknown loss-of-function mutations that confer cefuroxime resistance in K. pneumoniae isolates. The proteins lost were NlpD and KvrA; the latter is a transcriptional repressor that controls capsule production. We demonstrate that KvrA loss reduces OmpK35 and OmpK36 porin production, which confers reduced susceptibility to meropenem-vaborbactam in a KPC-3-producing K. pneumoniae isolate.